THE CONCEPT OF TEXTUAL GAPS - Prof. Dr. Bayan Shaker Juma (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This research tries to shed light on the concept of the gaps after a quick presentation of the concept of theory and how focused on the recipient after you try to view what the Arab heritage of signalsemphasize important of interest in the recipient , and then touched on research to critical points of the theory which is wayfor interaction between text and the recipient , and what needs this reaction of the elements in order to result in the true meaning of the text , and how it affects some factors on the quality of this interaction , and research touched on different concept of textual gaps between Arab critic and another , and effects of choice Translated of the term from Germany to English and to Arabic , and the relationship of the concept of gaps terms of a other provided by ISER , and how can a n identifies the recipient gaps ? What a their importance for the literature in general , and the recipient and the process of protrude text in particular .